Religious Segregation in Rural Urban Community: The Experiences from Cihampelas District, Indonesia - Roro Sri Rejeki Waluyajati (Khazanah Sosial, 2022)
This paper examines religious segregation in Desakota communities, especially in Cihampelas District, West Bandung Regency, West Java, Indonesia. The method used in this paper is a qualitative method through collecting data from literature review, observation, and interviews. The results of the research show that segregation of religious areas has taken place in this place from 1970 until now. The identity of religious organizations is essential for community members to determine where they will live and the social treatment they will receive. Conflicts and clashes became commonplace in the sacred pattern of the community in the Cihampelas District in the 1990s. Therefore, the social and economic changes that have occurred in society have changed many things, including the way of the religion of the people. In addition, there were significant changes in religious and religious patterns in the people in this region; before the 1990s, their sacred designs tended to be exclusive; meanwhile, after the 1990s, until now, the religious and religious patterns of society were more inclusive or characteristic types. This change in spiritual practice has created a neutral sacred zone with community members who are pluralist in faith in that area.